The Role of Yoga in Cardiovascular Prevention and Rehabilitation - A Structured Narrative Review - Kowalska, Marta; Dworak, Michał; Ciszewska, Wiktoria; Matyja, Mateusz; Kosztyła-Czech, Zofia; Mazur, Anna; Brodziak, Julia; Wiśniewski, Tomasz; Werenkowicz, Wiktor (Quality in Sport, 2026)
Background: Yoga is increasingly used as an adjunct mind–body intervention in cardiovascular prevention and rehabilitation, with proposed effects on stress regulation and autonomic balance. Aim: To summarize evidence on yoga-based interventions in cardiovascular disease and cardiac rehabilitation, focusing on clinical outcomes, patient-reported outcomes, and autonomic function. Material and methods: A focused narrative review of clinical trials and evidence syntheses evaluating yoga in coronary heart disease/post–myocardial infarction settings, arrhythmias, and chronic heart failure was performed. Evidence was synthesized qualitatively and grouped by clinical condition and outcome domain. Results: In paroxysmal atrial fibrillation, yoga interventions have been associated with reductions in arrhythmia burden and improvements in anxiety, depression, and quality of life in controlled studies. In coronary heart disease and secondary prevention, systematic reviews suggest improvements in selected cardiovascular risk factors and patient-centered outcomes, although confidence is limited by heterogeneity in yoga protocols, comparators, and endpoints. In post–myocardial infarction cardiac rehabilitation, randomized trials report feasibility of structured delivery and improvements in rehabilitation-related and psychosocial outcomes. In chronic heart failure, clinical studies and meta-analytic evidence indicate favorable changes in hemodynamic measures and autonomic indices, including heart rate variability. Conclusions: Yoga may offer adjunctive benefits for quality of life, psychological outcomes, autonomic function, and selected physiological measures, while evidence for hard clinical endpoints remains limited. Larger, standardized randomized trials with consistent outcome reporting are needed.